Human Suffering and Divine Abuse of Power in Lamentations : Reflections on Forgiveness in the Context of South Africa's Truth and Reconciliation Process - Stiebert, Johanna (Pacifica, 2003)
After summarizing the picture of divine brutality and lack of divine compassion found in every chapter of Lamentations, S. notes this portrait is not an isolated case in point. She then parallels Yhwh's actions against Jerusalem to cases heard before the Truth and Reconciliation Commission (TRC) established in South Africa in 1995 as part of the Promotion of National Unity and Reconciliation Act No. 34. Here, forgiveness is conditioned upon admission of wrongdoing and is designed to enhance the self-respect of victims and to guard against the erasure of victims' suffering. Finally, using TRC criteria, she concludes that Yhwh is not eligible for forgiveness since he is not repentant; however, he would be eligible for unconditional forgiveness, done on behalf of another, as taught in the NT. [Abstracted by: Diana V. Edelman] Abstract Number: OTA27-2004-FEB-509
Keywords: Major Prophets